2020
DOI: 10.3390/biom10050745
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Lysophosphatidic Acid Acyltransferase of Escherichia coli Produces Membrane Phospholipids with a cis-vaccenoyl Group and Is Related to Flagellar Formation

Abstract: Lysophosphatidic acid acyltransferase (LPAAT) introduces fatty acyl groups into the sn-2 position of membrane phospholipids (PLs). Various bacteria produce multiple LPAATs, whereas it is believed that Escherichia coli produces only one essential LPAAT homolog, PlsC—the deletion of which is lethal. However, we found that E. coli possesses another LPAAT homolog named YihG. Here, we show that overexpression of YihG in E. coli carrying a temperature-sensitive mutation in plsC allowed its growth at non-permissive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…S1). This is different from the phenotype of the E. coli yihG mutant, which is more motile than the wildtype cell and displays elevated flagellar expression [12]. E. coli YihG differs from PlsC4/PlsC5 in its substrate selectivity towards 18:1 [12].…”
Section: Table 1 Lpaat Homologs Used In the Phylogenetic Analysismentioning
confidence: 73%
See 2 more Smart Citations
“…S1). This is different from the phenotype of the E. coli yihG mutant, which is more motile than the wildtype cell and displays elevated flagellar expression [12]. E. coli YihG differs from PlsC4/PlsC5 in its substrate selectivity towards 18:1 [12].…”
Section: Table 1 Lpaat Homologs Used In the Phylogenetic Analysismentioning
confidence: 73%
“…The function of the putative acyltransferase YihG in E. coli remained unknown for a long time. However, we recently found it to be a putative ortholog of PlsC4 (39% identical) and demonstrated it as a novel LPAAT with a substrate specificity different from that of PlsC from E. coli [12]. As a BLAST search indicated that other bacteria such as Pseudomonas and Vibrio also have putative PlsC4/YihG ortholog(s), we expanded the scope of an ortholog search using the KEGG Ortholog Cluster database.…”
Section: Phylogenetic Analysis Of Plsc4 and Plsc5mentioning
confidence: 99%
See 1 more Smart Citation
“…The scope of this Special Issue is to cover recent advances in our understanding of the structures and functions of the bacterial flagellar motor derived from different bacterial species. This Special Issue includes ten review articles [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ] and eleven original research papers [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ] from well-known experts in the field.…”
mentioning
confidence: 99%
“…E. coli has another LPAAT homolog named YihG in addition to PlsC, which is essential for the growth of E. coli . Toyotake et al constructed a yihG null mutant (∆ yihG ) and provided evidence suggesting that YihG has specific functions related to flagellar assembly through the modulation of the fatty acyl composition of membrane phospholipids [ 24 ].…”
mentioning
confidence: 99%